(3aGFOI aj GdbQYIs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3aGFOI aj GdbQYI, hgj ef GdbhGYO GdedbGI HGdbHhd hdcfge de jSdchG ajgG eSdkcG efVHkWG hUQGWG eSJbjeGs
(3BNQgG (B:s
(3BNQgG(B: (3HedGMXI Cf GdRhL eKkdG EPG CQGO GSJUMGH CMOK RhLGJg GdUGdMI GdQGLMI HGdGSJWMGH aj Yde Gddg, hef GdeYdhe Cfg dG jecf GdhUhd HGdEUdM EdG HGdbQYIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis